Localized Surface Plasmons on Textiles for Non-Contact Vital Sign Sensing - Yang, Xin; Tian, Xi; Zeng, Qihang; Li, Zhipeng; Nguyen, Dat T.; Ho, John S. (IEEE transactions on antennas and propagation, 2022)
Radio frequency technologies are capable of remotely sensing human vital signs for broad applications in healthcare. However, their use during daily life is hindered by challenges such as environmental interference, low sensitivity, and nonideal form factors. Here, we report a radio frequency sensor made from a conductive textile that provides sensitive noncontact monitoring of vital signs. The sensor (13 cm2 in size) comprises a radial pattern of grooves that support spoof localized surface plasmon (LSP) modes and a ground plane with a complementary window that controls the sensor's interaction with the body. These spoof LSP modes provide a sharp resonant dip and a broadly tunable evanescent field that enables tracking of heartbeat and respiration via the |S_{11}| spectrum measured in a connector-free manner. We establish the optimal operating mode of the sensor and show that it provides a resonant frequency shift of 250 MHz for respiration and 100 MHz for heartbeat motions. Experiments with a healthy human subject show that the measured heart rate (HR) and respiration rate (RR) are in close agreement with gold standard sensors and are robust to daily activities performed while sitting.